05 ANALISIS TREND JAGUNG DI SULAWESI SELATAN - Jurnal Agribis; Satriani Satriani; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2021)
The objectives of this study are: (1) To find out the trend of production, prices, and demand for corn in South Sulawesi (2) To find out the estimated production, prices, and demand for corn in South Sulawesi in 2016 up to 2020. This research was carried out in the scope of Sulawesi South regarding trends in production, prices, and demand for corn. The determination of this research area was determined intentionally. The type of data used is secondary data obtained from the central statistical body for use in analysis purposes. This study uses trend analysis methods to predict or find out how much the production, price, and demand for corn in South Sulawesi in 2016 to 2020. The results of the study show that (1) the trend of production, prices, and demand for corn in South Sulawesi fluctuate ( 2) Estimated production, price, and demand for corn in South Sulawesi from 2016 to 2020 has increased.